DISTANCE LEARNING STRATEGY MODEL BASED ON INTERACTIVE ONLINE TEST GAME TO IMPROVE STUDENT LEARNING OUTCOMES - Fauzi, Muh; Boeriswati, Endry; Khaerudin, Khaerudin (IJBLE Scientific Publications Community Inc., 2023)
This study aimed to design a distance learning strategy based on interactive online test media on discrete mathematics material to improve student motivation and learning outcomes. The low motivation of students to learn mathematics is caused by the paradigm of mathematics which is not a core subject in the informatics department and requires mathematics teaching staff to use new strategies and media to increase student learning motivation. The research method is mixed with developing a distance learning strategy and then ends with a test of effectiveness with the experimental process. The results of strategy development include methods, media, and time management. The resulting way is Synchronous in the form of face-to-face virtual discussions and Asynchronous in the form of material arranged in a Learning Management System (LMS), while the media developed is LMS. The experimental results found that the significant value of paired samples test was 0.00 <0.05, which means that there were differences in student learning outcomes in the experiment and control classes. The average value of the experiment class is 84.04, and the control class is 66.35, which means that the learning outcomes of students who use distance learning based on interactive online test media of discrete mathematics are better than conventional methods. Then the results of observations and student responses to distance learning strategies based on interactive online test media were declared valid and effective